E pluribus unum: the potential of collaborative learning to enhance Microbiology teaching in higher education - Rutherford, Stephen (FEMS microbiology letters, 2015)
Collaborative learning, where students work together towards a shared understanding of a concept, is a well-established pedagogy, and one which has great potential for higher education (HE). Through discussion and challenging each other's ideas, learners gain a richer appreciation for a subject than with solitary study or didactic teaching methods. However, collaborative learning does require some scaffolding by the teacher in order to be successful. Collaborative learning can be augmented by the use of Web 2.0 collaborative technologies, such as wikis, blogs and social media. This article reviews some of the uses of collaborative learning strategies in Microbiology teaching in HE. Despite the great potential of collaborative learning, evidence of its use in Microbiology teaching is, to date, limited. But the potential for collaborative learning approaches to develop self-regulated, deep learners is considerable, and so collaborative learning should be considered strongly as a viable pedagogy for HE. Collaborative learning is a powerful approach that can enhance the depth, scope and impact of learning, this review evaluates the potential impact of collaborative learning on microbiology teaching in HE.